An approach to violence against women - Laguado Barrera, Tatiana (Mundo FESC, 2017)
Violence against women seen from a reflexive position, specifying their different edges and factors involved, a phenomenon that is dynamized in a complex way through the social and cultural constructs of inequality towards women. The article aims the approach to the factors associated with violence against women, from a gender perspective, exploring the effects that they have on women’s health. Little progress has been made in the implementation of law 1257 of 2008, and there have been serious difficulties that minimize the different expressions of violence. The structuring of programs is needed to achieve gender equality standards, better opportunities for women’s self-realization, and a strong legal framework that defends and reinstates the rights of victims.